Isotope and noble gas study of three aquifers in central and southeast Libya - Al Faitouri, Mohamed S. E., author; Sanford, William, advisor; Ronayne, Michael, committee member; Fassnacht, Steven, committee member; Waskom, Reagan, committee member (Colorado State University. Libraries, 2013)
To view the abstract, please see the full text of the document.
Keywords: 14C; noble gas; isotope